2020
DOI: 10.1021/acs.nanolett.9b04650
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Detection of Single Auger Recombination Events in a Self-Assembled Quantum Dot

Abstract: Auger recombination is a non-radiative process, where the recombination energy of an electron-hole pair is transferred to a third charge carrier. It is a common effect in colloidal quantum dots that quenches the radiative emission with an Auger recombination time below nanoseconds. In self-assembled QDs, the Auger recombination has been observed with a much longer recombination time in the order of microseconds.Here, we use two-color laser excitation on the exciton and trion transition in resonance fluorescenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
1
13
1
1
Order By: Relevance
“…The QD layer is embedded in a p-i-n diode structure with a highly n-doped GaAs layer as a charge reservoir and a highly p-doped GaAs layer as an epitaxial gate 34 . Between the charge reservoir and the QD, 45 nm (AlGa)As are implemented as tunneling barrier to achieve electron tunneling times in the order of milliseconds (see Lochner et al 28 for details about the sample structure). An applied voltage between charge reservoir and gate can control the charge state of the QD.…”
Section: Sample Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QD layer is embedded in a p-i-n diode structure with a highly n-doped GaAs layer as a charge reservoir and a highly p-doped GaAs layer as an epitaxial gate 34 . Between the charge reservoir and the QD, 45 nm (AlGa)As are implemented as tunneling barrier to achieve electron tunneling times in the order of milliseconds (see Lochner et al 28 for details about the sample structure). An applied voltage between charge reservoir and gate can control the charge state of the QD.…”
Section: Sample Design and Methodsmentioning
confidence: 99%
“…This scattering process is well known from colloidal QDs [22][23][24] and has been directly observed just recently in resonance fluorescence measurements 25 with Auger recombination rates in the order of microseconds. [26][27][28][29] In this paper, we show time-resolved resonance fluorescence (RF) measurements on the trion transitions of a a) Electronic mail: hendrik.mannel@uni-due.de negatively-charged InAs QD, embedded in an electrically controllable diode structure and charged by electron tunneling from a nearby charge reservoir. An applied magnetic field B of up to 10 T in Faraday geometry (here, parallel to the growth axis) splits the trion into a lower ("red") and a higher ("blue") energy transition.…”
Section: Introductionmentioning
confidence: 99%
“…bedded in a p-i-n diode structure (see Fig. 1(a), (b) and [16] for more details). The n + -doped back contact serves as an electron reservoir, separated from the QD by a tunnel barrier of 30 nm GaAs, 10 nm Al 0.33 Ga 0.67 As and 5 nm GaAs.…”
Section: Methodsmentioning
confidence: 99%
“…For example, timeresolved photoluminescence can be used to study charge * jens.kerski@uni-due.de fluctuations in colloidal nanocrystals at room temperature [13,14]. Also, resonant fluorescence at compared to the mK scale high temperatures (4.2 K) can be used to study tunneling [15] and Auger processes [16] in selfassembled quantum dots (QDs) as well as spin dynamics [17] in quantum dot molecules. The optical excitation of the single quantum emitter by resonant fluorescence offers a high energetic resolution, and the detection of the single photons with avalanche photodiodes or superconducting nanowire detectors promises a high bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Auger recombination is a non-radiative process in which the energy released during electron and hole recombination is transferred to a third charge carrier (either electron or hole) which is then excited to a higher energy state. [23][24][25] Alternatively, it has been shown that multiple electrons can be transferred from photoexcited QDs to different molecular acceptors, e.g. methylene blue (MB).…”
Section: Introductionmentioning
confidence: 99%